2019
DOI: 10.1186/s13613-019-0608-6
|View full text |Cite
|
Sign up to set email alerts
|

“I had the feeling that I was trapped”: a bedside qualitative study of cognitive and affective attitudes toward noninvasive ventilation in patients with acute respiratory failure

Abstract: Background: Noninvasive ventilation (NIV) is the application of mechanical ventilation through a mask. It is used to treat certain forms of acute respiratory failure in intensive care units (ICU). NIV has clinical benefits but can be anxiogenic for the patients. This study aimed at describing cognitive and affective attitudes toward NIV among patients experiencing NIV for the first time in the context of an ICU stay.Methods: Semi-structured interviews were conducted in 10 patients during their ICU stay and soo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 42 publications
0
14
0
7
Order By: Relevance
“…Iosifan et al provided patients with detailed information prior to NIV treatment and most patients did not have anticipatory anxiety or fear. 16 In our study, patients reported that discussing this therapy before it is needed is not necessarily good because it could inflict more fear for the future. This is similar to the findings of Beckert et al and Lemoigan et al that suggested patients do not want information about their treatment before it is needed to make decisions, because information tends to discourage them.…”
Section: Phase 4: After Niv Treatmentmentioning
confidence: 73%
See 1 more Smart Citation
“…Iosifan et al provided patients with detailed information prior to NIV treatment and most patients did not have anticipatory anxiety or fear. 16 In our study, patients reported that discussing this therapy before it is needed is not necessarily good because it could inflict more fear for the future. This is similar to the findings of Beckert et al and Lemoigan et al that suggested patients do not want information about their treatment before it is needed to make decisions, because information tends to discourage them.…”
Section: Phase 4: After Niv Treatmentmentioning
confidence: 73%
“…Prior studies reported that patients express anxiety, fear, claustrophobia, and feelings of lacking control. [15][16][17] However, most prior studies were performed outside the United States (different roles of clinical staff) or in non-COPD patients.…”
Section: Introductionmentioning
confidence: 99%
“…The concept of "eCASH" was proposed by the European association for critical care medicine to establish optimal patient comfort, which advocate flexible multimodal analgesia to relieve the pain effectively as the first priority [32]. Because of Patients with NIV experienced mask-related pain and expressed as "I had the feeling that I was trapped" [33], analgesia was necessary for NIV patients to relieve pain and facilitate the successful implementation of the NIV.…”
Section: Discussionmentioning
confidence: 99%
“…All participating units were general ICUs. There were an average of 34 (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39) beds in each ICU, accounting for 1.9% (1.7-2.2) of all hospital beds (Table 1). The protocol was approved by the Institutional Ethics Committee of Zhongda Hospital affiliated to Southeast University (the core center, Approval No.…”
Section: Methodsmentioning
confidence: 99%
“…Common barriers to NIV adaptation include dyspnea, mask discomfort, anxiety, and claustrophobia. 8 The current study included clinically stable outpatients who likely experience fewer communication obstacles than an individual in acute respiratory distress. Up to one third of patients on NIV for acute respiratory failure report significant anxiety.…”
mentioning
confidence: 99%